TRANSFORMATION OF UPLAND COTTON WITH PINELLIA TERNATA AGGLUTININ GENE AGAINST SUCKING PESTS - S. Ahmed; I. A. Nasir (Journal of Animal and Plant Sciences, 2021)
Cotton plants are normally targeted by numerous challenges from which 75% are biotic. Among these biotic stresses, insects constitute major segment causing direct or indirect considerable yield loss. Bt cotton, corn and soybean are mostly resistant to chewing insects in the field, but their resistance to sap sucking pests has not yet achieved. Likewise Bt protein against chewing insect, there are some proteins characterized for their actions against sucking insects e.g. lectins. Major function of plant lectin is to provide anti-insect activity with other known and unknown function. Therefore, all necessary in-silico, in-vivo and plant transformation experimentation adopted to design a codon optimized (cotton targeted) Pinellia ternata agglutinin (pta) gene cassette under the influence of well-tested CaMV35S promoter in pCAMBIA2300 expression vector enabled by agrobacterium LB4404 plant infecting strain for stable delivery and integration of transgene in the recipient genome. Stable transformation of at least five different cotton plants (transformation efficiency 0.53%) took place successively, which was tested through PCR and Southern blotting in T0 and T1 generation. This work has provided genotypic bases and a candidate phenotype of commercial cotton crop resistant against sucking pests.
Keywords: Nuclear Transformation; Pinellia ternata agglutinin; Cotton